Detecting legionellosis by unselected culture of respiratory tract secretions and developing links to hospital water strains - Köhler, Julia Ruth; Maiwald, Matthias; Lück, P. C.; Helbig, J. H.; Hingst, Volker; Sonntag, Hans-Günther (The journal of hospital infection, 1999)
For a 13-month period, all respiratory tract secretions submitted for routine bacteriology from a large hospital complex were cultured for legionella, irrespective of clinical diagnosis and laboratory requests. Ten cases of legionellosis were detected in this manner, three of which met a strict epidemiological definition of hospital-acquired. Therefore, the 16 warm-water systems of the hospitals, spread out over two locations, were examined for the presence of legionella. Legionella pneumophila was found in 15 warm water systems, with a distinct pattern of serogroups between the two locations. Legionella of the same serogroups as those isolated from patients were present in each hospital water supply. The isolates were further typed by monoclonal antibodies and by genomic macrorestriction analysis. Similarity between clinical and environmental isolates was found in seven cases. In these cases, acquisition from the hospital water supply appears very likely. The strains of the remaining three patients did not match those in hospital water, suggesting that community-acquired legionellosis was occurring as well. This study suggests that routinely culturing respiratory tract secretions of pneumonia patients for legionella can help diagnose unsuspected cases of legionellosis. Typing legionella strains beyond the serogroup level with tools such as macrorestriction analysis is useful to define sources of infection, which can then be targeted for control measures.
Gesehen am 22.03.2021